Subversive narrative techniques and self-reflexivity in Vladimir Nabokov's the real life of Sebastian Knight, Lolita, Pnin, Pale Fire and Ada, or Ardor: A family Chronicle - Meier, Björn (Department of English Language and Literature, 2016)
This dissertation has three aims. First, the establishment of the theoretical foundations of deconstruction and its appropriation by literary criticism. Second, the application of deconstruction to the novels of Nabokov; it has to be stressed that this application is not itself a deconstructive reading, rather that deconstruction offers the interpretative horizon for an analysis of the inner logic of self-reflexivity in the novels in question. which is defined with de Man and against Derrida as a procedure of textual self-deconstruction. The procedure, evident in the proliferation of textual strategies in Nabokov's work, marks the point at which literary modernism transforms itself through the radicalisation of the critique of narrative, subject and meaning into a postmodern aesthetics of deconstruction. The interpretation of the novels then serves thirdly to pose the question of the value of the theory of deconstruction for the task of interpretation, or more generally. the value of deconstruction for literary theory. The interpretation of Nabokov's novels reveals a paradox: selfdeconstructive literature does not require a deconstructive reading. On the contrary, the textual deconstruction of meaning and reference requires the non-deconstructive standpoint of a coherent literary analysis for its demonstration. Comparably and conversely, a deconstructive reading presupposes a text and/or an author committed to the intention of a meaningful whole (however ambiguous). The author's distinction between deconstruction as a method of interpretation and as a literary theory thus points to the limitations of deconstruction as interpretative method in relation to modern and postmodern texts precisely because of their metafictional affinity to deconstruction. Beyond this, however, deconstruction's treatment of the text as pretext for its own operations, taken to its logical conclusion, would dissolve the very cognitive object and interest of literary studies.